Between work and project: situated knowledge, art technologies and new specialisations (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
The relationship between multimedia artistic work, situated knowledge, and project is discussed. The case study of Santa Marta (Venice) is explored in depth, between the ‘presence effect’ and the ‘meaning effect.’ It is concluded that attention to the culture of the between in artistic practices produces more conscious and responsible digital art, geared towards new experiments and spatialities, attentive to hybridisations, the invisibilities of concepts and the non-visibility of algorithms.
Keywords: Multimedia design; new spatiality; affective atmospheres; immersive experience; post-qualitative research